Evolutionary prediction of novel biphenylene networks as an anode material for lithium and potassium-ion batteries - Adewale Hammed Pasanaje; Nirpendra Singh (Nano Materials Science)
The discovery of novel materials with compelling properties is more accessible with the help of advanced computational algorithms. Recent experimental synthesis of the biphenylene network (C6) motivated us to discover new BN-doped biphenylene networks (C4BN, C2B2N2, and B4N4) and their applications in Li(K)-ion batteries using an evolutionary algorithm and the first-principles calculations. The thermodynamic, thermal, and mechanical stability calculations and decomposition energy suggest the experimental synthesis of predicted biphenylene networks. Adding BN in the biphenylene networks shows a transition from metal to semimetal to semiconductor. The BN biphenylene network shows an HSE06 band gap of 3.06 ​eV, smaller than h-BN. The C4BN and C2B2N2 biphenylene networks offer Li(K) adsorption energy of −0.56 ​eV (−0.81 ​eV) and −0.14 ​eV (−0.28 ​eV), respectively, with a low diffusion barrier of 178 ​meV (58 ​meV) and 251 ​meV (79 ​meV), and a large diffusion constant of 8.50 ​× ​10−5 cm2/s (8.78 ​× ​10−3 cm2/s) and 5.33 ​× ​10−6 cm2/s (4.12 ​× ​10−3 cm2/s), respectively. The calculated Li(K) theoretical capacity of C4BN and C2B2N2 biphenylene networks is 940.21 ​mA ​h ​g−1 (899.01 ​mA ​h ​g−1) and 768.08 ​mA ​h ​g−1 (808.47 ​mA ​h ​g−1), with a low open circuit voltage of 0.34 ​V (0.23 ​V), and 0.17 ​V (0.13 ​V), resulting in very high energy density of 2576.18 ​mW ​h ​g−1 (2445.31 ​mW ​h ​g−1) and 2181.35 ​mW ​h ​g−1 (2263.72 ​mW ​h ​g−1), respectively. Only a slight volume change of 1.6% confirms the robustness of BN-doped carbon-based biphenylene networks. Our findings present novel 2D BN-doped biphenylene networks and a pathway toward their applications in metal-ion batteries.